QUANTITATIVE YIELD IN SAWING THIN LOGS OF SCOTS PINE (PINUS SYLVESTRIS L.) FOR PRODUCTION OF DIMENSIONAL LUMBER WITHOUT DEFECTS - Trichkov, Neno; Koynov, Daniela (Innovation in Woodworking Industry and Engineering design, 2018)
This paper presents experimental work results on establishing the quantitative yield of sawing thin round Scots pine (Pinus sylvestris L.) logs for production of dimensional lumber without defects. The experimental work was performed on thin logs obtained from the top part of tree stems. These were examined for the presence of the wood defects, their size and number. Following the normal production sequence, the thin logs were sawn into lengths of 500, 800, 1000 and 1200 mm. These, in turn, were plain sawn into boards and after that into dimensional lumber with widths of 3, 6 and 9 mm. The obtained pieces were analysed and conclusions were drawn on the quantitative wood yield depending on pieces’ thickness and length. The data allow to evaluate more accurately and objectively the technology and machinery in order to ensure more efficient processing of thin roundwood.